Comparison of Cobit 4.1 With Cobit 5 in Payment System System X at University YZ - Sartin Sartin; Yusup Yusup; Satrio Agung Prakoso (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
The increasing reliance on information systems in higher education requires effective information technology (IT) governance to ensure system reliability, security, and alignment with institutional objectives. One of the critical systems in universities is the digital payment system used for managing student financial transactions. This study aims to compare the effectiveness of the COBIT 4.1 and COBIT 5 frameworks in evaluating IT governance within the X Payment System at YZ University based on user perceptions. A quantitative approach was employed by distributing questionnaires to 82 student respondents who actively use the system. The evaluation applied the Deliver and Support (DS) and Monitor and Evaluate (ME) domains of COBIT 4.1, as well as the Deliver, Service, and Support (DSS) and Monitor, Evaluate, and Assess (MEA) domains of COBIT 5. The analysis results indicate that the average maturity level of the system based on COBIT 4.1 reached 3.87, categorized as Level 4 (Managed and Measurable), while the COBIT 5 capability assessment obtained an average score of 3.83, categorized as Level 4 (Predictable Process). The highest performance scores were observed in data integrity and system security processes, indicating strong user trust in the accuracy and protection of financial data. These findings demonstrate that the payment system has been consistently managed, monitored, and evaluated. The study concludes that COBIT 4.1 is effective in mapping operational procedures and control structures, whereas COBIT 5 provides a more comprehensive governance perspective by integrating operational performance with organizational value creation. Recommendations include implementing automated real-time monitoring and strengthening infrastructure capacity to maintain system stability during peak transaction periods.